The Impact of Yoga Intervention on Physical and Mental Health of Adults with Type 2 Diabetes - Poongothai Subramani; Anjana Ranjit Mohan; Latha Satish; Swetha Karthikeyan; Pavithra Ravi; Venkatesan Ulagamathesan; Viswanathan Kannikan; Mohan Viswanathan (International Journal of Yoga)
Aim: To assess the impact of a yoga intervention on the physical and mental health of adults with type 2 diabetes. Methods: This study was conducted at Madras Diabetes Research Foundation, Chennai, for 6 months. Participants aged 18–65 years, diagnosed with type 2 diabetes mellitus (T2DM), and glycated hemoglobin (HbA1c) levels ranging from ≥7.0% to ≤10.5% were recruited. One hundred and fifty-two participants were randomized in 1:1 ratio to either the intervention or control arm by simple random method. The intervention included structured yoga practice for 35 min, every 2 weeks for a period of 12 weeks, and followed up for 3 months. Participants in the control arm received the standard care for diabetes. Sociodemographic data, anthropometric measurements, and blood samples were collected at baseline and final visit. Standard questionnaires were administered for assessing mental health parameters. Results: 53 of 76 (70%) participants from the intervention arm and 70 of 76 (92%) participants from the control arm completed the study. The mean age of the participants was 53 ± 7.5 years. The mean duration of diabetes of the participants was 10 ± 6.9 years. HbA1c showed reduction postintervention, but this was not statistically significant compared to control. The intervention group showed statistically significant improvements in depression, stress, cognitive function, and mindfulness compared to the control arm. Conclusion: Yoga is helpful in reducing depression and stress and enhancing mindfulness and cognitive function in patients with T2DM.